Reflections : life after the White House - Bush, Barbara. 1925-2018. (New York : Scribner, 2003)
The author traces the eight years between the presidencies of her husband and son, discussing her charity work, relationships with her children and grandchildren, and her family's reactions to September 11 and its aftermath
"A Lisa Drew book."
Includes index
Keywords: Bush, Barbara, 1925-; Bush, George, 1924-; Presidents' spouses -- United States -- Biography; Bush families. -- Biography